Conformational characterization of the intrinsically disordered protein Chibby: Interplay between structural elements in target recognition. (1st May 2016) - Killoran, Ryan C.; Sowole, Modupeola A.; Halim, Mohammad A.; Konermann, Lars; Choy, Wing‐Yiu
Abstract: The protein Chibby (Cby) is an antagonist of the Wnt signaling pathway, where it inhibits the binding between the transcriptional coactivator β‐catenin and the Tcf/Lef transcription factors. The 126 residue Cby is partially disordered; its N‐terminal half is unstructured while its C‐terminal half comprises a coiled‐coil domain. Previous structural analyses of Cby using NMR spectroscopy suffered from severe line broadening for residues within the protein's C‐terminal half, hindering detailed characterization of the coiled‐coil domain. Here, we use hydrogen/deuterium exchange‐mass spectrometry (HDX‐MS) to examine Cby's C‐terminal half. Results reveal that Cby is divided into three structural elements: a disordered N‐terminal half, a coiled‐coil domain, and a C‐terminal unstructured extension consisting of the last ∼ 25 residues (which we term C‐terminal extension). A series of truncation constructs were designed to assess the roles of individual structural elements in protein stability and Cby binding to TC‐1, a positive regulator of the Wnt signaling pathway. CD and NMR data show that Cby maintains coiled‐coil structure upon deletion of either disordered region. NMR and ITC binding experiments between Cby and TC‐1 illustrate that the interaction is retained upon deletion of either Cby's N‐terminal half or its C‐terminal extension. Intriguingly, Cby's C‐terminal half alone binds to TC‐1 with significantly greater affinity compared to full‐length Cby, implying that target binding of the coiled‐coil domain is affected by the flanking disordered regions.